"Sleep Surge": The impact of sleep onset and offset on epileptiform discharges in idiopathic generalized epilepsies. Issue 5 (May 2020) - Seneviratne, Udaya; Lai, Alan; Cook, Mark; D'Souza, Wendyl; Boston, Ray C.
Highlights: A cohort of patients with idiopathic generalized epilepsy (IGE) has been studied. The epileptiform discharge rate increases with sleep-onset and drops with awakening. Duration of seizure freedom, antiepileptic drugs and age do not impact this pattern. Abstract: Objective: To investigate the impact of sleep onset and offset on the rate of epileptiform discharges (ED) in idiopathic generalized epilepsies (IGE). Methods: We studied the temporal distribution of EDs with mixed-effects Poisson regression modeling in a cohort of patients diagnosed with IGE who underwent 24-hour ambulatory electroencephalography (EEG) recordings. We defined the mean number discharges per hour per subject as the mean ED rate. The association between each hour and the mean ED rate was quantified with incidence rate ratio (IRR) as the metric. We calculated the IRR of each hourly block for the total cohort in relation to sleep onset and offset. Finally, we admitted secondary risk factors into our Poisson regression model and quantified changes in IRR in order to investigate the impact of those variables on the outcome. The secondary risk factors included: epilepsy syndrome, duration of seizure freedom, duration of epilepsy, number of antiepileptic drugs (AED), type of AED, and age. Results: A total of 39 patients with a mean age of 29.1 y (SD = 10.1) were studied. The distribution of ED rate demonstrated a highly significant abrupt increase in the first hour after sleep onset (IRR = 3.96; p < 0.001). On the contrary, the ED rate significantly dropped in the second hour after the sleep offset compared with the last hour block before sleep offset (IRR = 0.39; p < 0.001). None of the secondary risk factors demonstrated any significant impact on this pattern. Conclusions: Sleep onset is a very significant trigger for the generation of EDs in IGE. Significance: Our results support the hypothesis that there is a "critical zone of vigilance" in the sleep-wake boundary from which generalized EDs are more likely to emerge.